ANALYSIS AND MODELLING OF GRAVITY- AND PISTON CORING BASED ON SOIL MECHANICS - Skinner L.C.; McCave I.N. (My University, 2003)
The effects of gravity- and piston corers on the dimensional accuracy of marine sediment cores is analysed using principles of soil mechanics. A model for the coring process is built around the feedback that arises and develops between the core barrel and the sampled sediment. This model for sediment response is applied to different hypothetical coring scenarios, which are then compared to real examples, providing insights into the specific effects of each sampling method and the development of these effects down-core. Four cores from a single location on the Iberian Margin are found to contain stratigraphically intact successions that differ in length by a factor of up to 2.7, due solely to the different effects of each coring method. These dimensional discrepancies are attributed to the combined effects of 'over-sampling' in the upper portions of the piston cores (due to cable rebound causing upward piston acceleration), and 'under-sampling' dominant in the basal portions of the open-barrel gravity-type cores. It is suggested that heavier piston corers, deployed on longer, lighter cables, are prone to greater over-sampling ratios over longer stratigraphic intervals, due to the increased likelihood and extent of cable rebound. Cable rebound may also give rise to double penetration of gravity corers, resulting in repeated stratigraphic intervals. Knowledge of the dimensional accuracy of marine sediment cores is essential to an evaluation of past sedimentation rates, and hence interpretations of past depositional processes. It is therefore essential that we recognise the sampling effects of each coring method, and their variability down-core, lest coring artefacts be interpreted as sedimentary signals. Different core types may be more suited to different palaeoceanographic investigations. Hence, failing the development of a practical cable-deployed recoilless piston corer, a combination of a variety of core types will permit the best acquisition of the in situ stratigraphic truth. Our results suggest that a large-diameter (Dc~20-30 cm) square-barrel gravity corer for the top 10-12 m combined with a cylindrical piston corer below ~10 m may provide the least deformed material.
Keywords: CORING; SOIL MECHANICS; PISTON; IMAGES; CALYPSO; KASTEN